Nanodelci: sodobni dostavni sistem za učinkovine in antigene celicam imunskega sistema - Obermajer, Nataša (Farmacevtski vestnik, 2007)
As the immune cells are distributed in bodily fluids and tissues throughout the organism, they represent a moving target for drug delivery. In this case aclassical approach applying high doses of the drug is not appropriate and, therefore, the use of nanoparticles represents a good alternative to avoid, orat least decrease its side effects and increase efficacy. Nanoparticles can be used as an efficient delivery system to enhance the uptake of antigens by antigen presenting cells as well as to target specific lymphocyte populations.With such approach we can regulate the immune function or merely exploit the function of immune cells to improve efficacy of drug loaded nanoparticles in treatment of infected or malignant transformed cells.
Keywords: dostava zdravilnih učinkovin; drug; nanodelci; zdravila